Анализ медицинских последствий чрезвычайных ситуаций в одесской области за 2001-2005 годы - Манюта, А.В. (Актуальні проблеми транспортної медицини, 2006)
За даними ВОЗ травми і отруєння в світі є другою причиною смерті та інвалідності серед працездатного населення після серцево-судинної патології. кількості пожеж і спалахів кількість померлих від травм і травмованих за період з 2001 по 2005 роки зростає. Необхідно організувати облік і провести соціально-гігієнічний моніторинг потерпілих при надзвичайних ситуаціях, які крім або незалежно від отримання травм захворіли соматичними, психосоматичними захворюваннями або одержали психічні травми. By WHO's data, traumas and venenatings in the world are the second cause of mors and physical inability among able-bodied population after a cardiovascular pathology. The similar statistical data are resulted by Central administrative board of the Ministry of Emergency Measures of Ukraine in the Odessa region. Despite the fact that number of fires decrease the quantity of deaths owing to traumas and injured during fires for last years grows. It is necessary to organize the count and to manufacture social - hygienic monitoring somatic, psychosomatic diseases or the mental traumas those have gotten at extreme situations.